Investigation of Performance Specifications for Marshall Mixes Using Performance-Based Mix Design Methodology - Shaikh S.; Gupta A.; Saboo N. (My University, 2025)
This paper presents a comprehensive study for developing the performance specifications for the Marshall mixes using the performance-based mix design (PMD) methodology. The specification describes the desired levels of fundamental engineering properties for predicting performance during mix design or quality assurance checks at the time of construction. In this study, the bituminous concrete mixture was designed through complementing volumetric criteria with performance tests such as dynamic creep and the indirect tensile asphalt cracking test for evaluating resistance against rutting and fatigue cracking, respectively. This study considers different factors such as five different types of design aggregate gradations (mid-gradation, fine-coarse gradation, coarse gradation, coarse-fine gradation, and fine gradation), three binder types (VG-30, VG-40, and PMB-40), and five levels of compactive efforts (35, 50, 75, 90, and 110 blows on each face). The study finds the effect of design aggregate gradation, binder type, and compactive effort on the rutting and cracking resistance of bituminous mixes. The research study also comprehends the influence of volumetric properties on the performance parameters. Further, it establishes the initial performance criteria for rutting and cracking for Marshall mixes. The performance space diagram (PSD) has also been plotted, portraying the overall performance (acceptable, desirable, or unsatisfactory performance regions) of bituminous mixtures based on rutting resistance and cracking resistance. This paper highlights and advocates the integration of these performance-based specifications into the Marshall mix design specifications for improving pavement characteristics and extending overall service life. © The Author(s) 2024.